Manajemen Kurikulum Berbasis Deep Learning dalam Meningkatkan Motivasi Belajar Siswa - Saptono, Puput; Musolin , Muhlil; Achmad Sopian (Kartika: Jurnal Studi Keislaman, 2026)
Education plays a strategic role in improving the quality of human resources and shaping students’ character and morality. However, low learning interest and motivation remain major challenges, particularly due to conventional instructional approaches that fail to actively engage students. In the digital era, these challenges are further intensified by distractions from gadgets and social media. Therefore, innovation in learning management is required, one of which is through deep learning-based curriculum management. This study aims to analyze the role of deep learning curriculum management in enhancing students’ learning motivation at SMP N 2 Buluspesantren, Kebumen Regency. The deep learning approach emphasizes in-depth conceptual understanding, interconnected knowledge construction, and learning experiences that are mindful, meaningful, and joyful. By integrating educational technology, this approach enables personalized learning that accommodates students’ needs and learning styles. The findings indicate that the implementation of deep learning-based curriculum management contributes to the creation of a more flexible, interactive, and meaningful learning environment, which positively affects students’ engagement and motivation. Despite challenges such as technological dependency and limited face-to-face social interaction, this approach is considered effective in fostering learning motivation. This study is expected to serve as a reference for developing innovative curriculum management strategies to improve educational quality